Dynamic chest radiography for pulmonary vascular diseases: clinical applications and correlation with other imaging modalities - Yamasaki, Yuzo; Kamitani, Takeshi; Sagiyama, Koji; Hino, Takuya; Kisanuki, Megumi; Tabata, Kosuke; Isoda, Takuro; Kitamura, Yoshiyuki; Abe, Kohtaro; Hosokawa, Kazuya; Toyomura, Daisuke; Moriyama, Shohei; et al. (Japanese journal of radiology, 2024)
Dynamic chest radiography (DCR) is a novel functional radiographic imaging technique that can be used to visualize pulmonary perfusion without using contrast media. Although it has many advantages and clinical utility, most radiologists are unfamiliar with this technique because of its novelty. This review aims to (1) explain the basic principles of lung perfusion assessment using DCR, (2) discuss the advantages of DCR over other imaging modalities, and (3) review multiple specific clinical applications of DCR for pulmonary vascular diseases and compare them with other imaging modalities.